Assessing COVID-19 Vulnerability Among HIV-positive Men Who Have Sex With Men in Korea: The Role of Vaccination and Sexual Behaviors - Minsoo Jung (Korean Society for Preventive Medicine, 2024)
Objectives: Comorbidities increase susceptibility to severe coronavirus disease 2019 (COVID-19) infections, but limited information has been published regarding human immunodeficiency virus (HIV) and COVID-19 co-infections. This study explored the relationships among socioeconomic characteristics, sexual behaviors, and COVID-19 infection rates among Korean men who have sex with men (MSM) who are also living with HIV. Methods: Data were collected through a web survey aimed at members of the largest gay portal site in Korea, supported by the National Research Foundation of Korea (n=1005). The primary independent variables included COVID-19-related vaccinations and sexual behaviors. The dependent variable was the incidence of COVID-19 infection among respondents during the pandemic. For statistical analysis, hierarchical multiple logistic regression was performed, controlling for potential confounding variables. Results: Model I indicated that older MSM were less likely to contract COVID-19 (adjusted odds ratio [aOR], 0.98; 95% confidence interval [CI], 0.96 to 0.99). Model II demonstrated that HIV-positive MSM were nearly twice as likely to be infected with COVID-19 compared to their HIV-negative counterparts (aOR, 1.97; 95% CI, 1.14 to 3.41). Furthermore, even after accounting for COVID-19 vaccination status in model III, HIV-positive MSM continued to show a higher risk of infection (aOR, 1.93; 95% CI, 1.12 to 3.35). Conclusions: The findings of this study indicate that HIV-positive MSM are at an increased risk of contracting COVID-19, even when their vaccination status is considered. Therefore, it is essential to prioritize the prevention of COVID-19 infections in HIV-positive individuals by administering appropriate antiretroviral therapy and ensuring adherence to public health guidelines.